Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/inf.0b013e31824da716
|View full text |Cite
|
Sign up to set email alerts
|

Application of the World Health Organization Criteria to Predict Radiographic Pneumonia in a US-based Pediatric Emergency Department

Abstract: The WHO criteria demonstrated poor sensitivity for the diagnosis of radiographic pneumonia in a US-based pediatric emergency department. Compared with respiratory rate, oxygen saturation offered slightly improved test characteristics. Although applied to a different target population, these findings suggest the WHO criteria may not be a sensitive screening tool for the diagnosis of pneumonia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…17 In contrast, the WHO case definition had a specificity of 78% in more than 1,300 children in Malawi, while the specificity was 74% among children presenting to an emergency department in the United States. 35, 36 Consistent with these latter studies, we observed primary endpoint pneumonia or other (non-end-point) infiltrates on chest radiograph in 76% of children identified using WHO clinical criteria. The conflicting results across studies may reflect differences in the study populations, variable application of the WHO case definition, or variation in the interpretation of chest radiographs.…”
Section: Discussionsupporting
confidence: 81%
“…17 In contrast, the WHO case definition had a specificity of 78% in more than 1,300 children in Malawi, while the specificity was 74% among children presenting to an emergency department in the United States. 35, 36 Consistent with these latter studies, we observed primary endpoint pneumonia or other (non-end-point) infiltrates on chest radiograph in 76% of children identified using WHO clinical criteria. The conflicting results across studies may reflect differences in the study populations, variable application of the WHO case definition, or variation in the interpretation of chest radiographs.…”
Section: Discussionsupporting
confidence: 81%
“…A recent study of lung aspirates in children with CAP in the Gambia showed S. pneumoniae in 90% of the samples, yet this was prior to introduction of PCV and most detected pneumococci were serotypes included in the PCV 35. They did not find any hMPV which might indicate that the aetiology of CAP in high- and low-income countries differ 10. This is further supported by the low detection rate of hMPV (3%) in the study by Berkley et al 5 on Kenyan children with severe CAP.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, childhood CAP is difficult to diagnose. The Integrated Management of Childhood Illness (IMCI) diagnostic guidelines for the clinical diagnosis of CAP, developed by the WHO, have been important to reduce mortality, yet they lack sensitivity and specificity and might introduce misclassification bias in epidemiological studies 10. The gold standard today is diagnosis based on radiographic findings, which is the preferred method of case definition in epidemiological studies 11…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in US emergency departments have shown that WHO criteria used to diagnose radiological pneumonia lack sensitivity and specificity [42] and that tachypnea did not discriminate between children with positive and negative chest X-ray [43]. In a systematic review and meta-analysis, fast breathing and lower chest wall indrawing showed poor diagnostic performance [44].…”
Section: Discussionmentioning
confidence: 99%